The goal is to get x by itself. All we need to do is work around it.
1. -5x + 2 = 67
2. The reversed operation, or the opposite operation, for addition is subtraction. Thus subtract 2 from 67 and 2. The 2 should cancel itself out. -5x + [2-2=0] = 67 - 2 = 65 -> -5x = 65.
3. The reversed operation, or the opposite operation of multiplication is division. Thus divide 65 and-5 as well as -5 and -5. [-5/-5x = 1x. 1x -> 1 * x = x.] = 65/-5 = -13 -> x = -13.
4. Check your answer by plugging in -13 where x is. Solve with pemdas.
-5(13) + 2 = 67 -> 65 + 2 = 67 -> 67 = 67. Therefore the answer is -13.